2009
DOI: 10.1128/aac.00062-08
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial Activity of 1,3,4-Thiadiazolium-2-Aminide in Mice Infected withLeishmania amazonensis

Abstract: The efficacy of two mesoionic derivatives (MI-H-H and MI-4-OCH 3 ) was evaluated in CBA/J mice infected with Leishmania amazonensis. Treatment with these compounds demonstrated that the MI-4-OCH 3 derivative and the reference drug meglumine antimoniate (Glucantime) presented significant activity relative to an untreated control. No apparent hepatic or renal toxicity due to these mesoionic compounds was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 23 publications
0
15
0
3
Order By: Relevance
“…Some mesoionic derivatives such as 42, 43, 44 and 45 have already been studied to determine their antiparasitic activity and very potent or potent antileishmanial activities have been shown for all derivatives against three Leishmania species (L. amazonensis, L. braziliensis and L. chagasi) as compared to pentamidine as a standard drug (48,95,96). Their effect on the TryR activity of three Leishmania species was also investigated and the nitroderivative (45) provided very promising results (89).…”
Section: -Amino-134-thiadiazole Derivatives As Trypanothione Reducmentioning
confidence: 99%
“…Some mesoionic derivatives such as 42, 43, 44 and 45 have already been studied to determine their antiparasitic activity and very potent or potent antileishmanial activities have been shown for all derivatives against three Leishmania species (L. amazonensis, L. braziliensis and L. chagasi) as compared to pentamidine as a standard drug (48,95,96). Their effect on the TryR activity of three Leishmania species was also investigated and the nitroderivative (45) provided very promising results (89).…”
Section: -Amino-134-thiadiazole Derivatives As Trypanothione Reducmentioning
confidence: 99%
“…Additionally, in vivo studies made in the mouse L. amazonensis cutaneous infection model showed that the 4-methoxy derivative 38 exhibited comparable activity to the reference drug, meglumine antimoniate [70]. The derivative 38 was more effective than the non-substituted derivative 37 .…”
Section: Antileishmanial Activity Associated With 2-amino-134-thmentioning
confidence: 99%
“…At the 10th week post infection, there was an increased difference in footpad swelling between the mice treated with the test compound 38 (derivative 38 , lesion size ≈ 3 mm; derivative 37 , lesion size ≈ 6 mm) or meglumine antimoniate (lesion size ≈ 4 mm) and untreated infected mice (lesion size ≈ 7 mm), respectively. At the 12th week post infection, the results showed significantly differences between the groups of mice treated with test compounds (derivative 38 , lesion size ≈ 6 mm; derivative 37 , lesion size ≈ 9 mm) or meglumine antimoniate (lesion size ≈ 7 mm) and untreated infected mice (lesion size ≈ 14 mm), respectively [70]. The authors concluded that no significant differences in lesion size were observed in the groups treated with mesoionic compounds or meglumine antimoniate [70].…”
Section: Antileishmanial Activity Associated With 2-amino-134-thmentioning
confidence: 99%
See 2 more Smart Citations